Quality: a Literature Review in Scope Meet Marketing (Revista Brasileira Multidisciplinar, 2012)
The quality construct has been widely researched in the marketing literature focused on understanding the gap between what consumers expect and what is actually perceived. This paper presents a literature review of the 20 articles presented at the four Encontros de Marketing (EMAs) sponsored by Associação Nacional dos Cursos de Pós-Graduação em Administração (ANPAD), which mentioned the word quality in their titles. The alternative constructs most widely used to support the studies were satisfaction and loyalty / trust / commitment; and the studies that were analyzed seldom contained similar references. As a suggestion for future studies, a similar research in the context of the Encontros da ANPAD is proposed.
Keywords: Literature review; Quality; Perceptions; Consumer behavior